Pengaruh Harga dan Promosi Terhadap Keputusan Pembelian Kopi Bubuk Cap Mawar pada Masyarakat di Desa Banyuatis - Sukmayanti, Putu Aristya; Sujana, I Nyoman (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This study aims to find out (1) the influence of price on purchase decisions, (2) the influence of promotion on purchase decisions, and (3) the influence of price and promotion on purchase decisions. The population in this study is the community in Banyuatis Village which amounts to 3,406 people. The sampling technique in this study uses the purposive sampling technique with the number of samples used as many as 120 people. The data collection method used a questionnaire and was analyzed using multiple linear regression analysis. The hypothesis test used a t-test and an F-test which was processed with the help of the Statistical Package for The Social Science (SPSS) software device version 25. The results of the study show that (1) price has a positive and significant effect on the purchase decision of Cap Mawar coffee powder, (2) promotion has a positive and significant effect on the purchase decision of Cap Mawar coffee powder, and (3) price and promotion have a positive and significant effect on the purchase decision of Cap Mawar coffee powder.